2016
DOI: 10.1158/1078-0432.ccr-15-2714
|View full text |Cite
|
Sign up to set email alerts
|

Development of Engineered T Cells Expressing a Chimeric CD16-CD3ζ Receptor to Improve the Clinical Efficacy of Mogamulizumab Therapy Against Adult T-Cell Leukemia

Abstract: Purpose: Mogamulizumab (Mog), a humanized anti-CC chemokine receptor 4 (CCR4) mAb that mediates antibody-dependent cellular cytotoxicity (ADCC) using FcγR IIIa (CD16)-expressing effector cells, has recently been approved for treatment of CCR4-positive adult T-cell leukemia (ATL) in Japan. However, Mog failure has sometimes been observed in patients who have accompanying chemotherapy-associated lymphocytopenia. In this study, we examined whether adoptive transfer of artificial ADCC effector cells combined with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Previous studies using conventional CARs have reported attenuated activation signaling due to the formation of longer immunological synapses and variations in the antigen location and density on target cells [31,32]. Interestingly, recent reports highlight the effective formation of the immunological synapse and consequent T cell activation using different modular CAR formats, demonstrating a surprising plasticity and variability of such approaches [3,33,34]. Here, we demonstrate that the immunological synapse formed by the large αSTn-IgG4 TMs does not affect the activation nor cytotoxic potential of UniCAR T-cells targeting the STn antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using conventional CARs have reported attenuated activation signaling due to the formation of longer immunological synapses and variations in the antigen location and density on target cells [31,32]. Interestingly, recent reports highlight the effective formation of the immunological synapse and consequent T cell activation using different modular CAR formats, demonstrating a surprising plasticity and variability of such approaches [3,33,34]. Here, we demonstrate that the immunological synapse formed by the large αSTn-IgG4 TMs does not affect the activation nor cytotoxic potential of UniCAR T-cells targeting the STn antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies have been the focus of many engineering efforts likely due to the rapidly deployable and highly generalizable nature of mAbs with relatively little attention paid to FcgRs themselves (55). Though FcgRs provide useful modules for chimeric protein design, these designs generally do not enhance FcgR functionality and, with one exception, will not be discussed here (a few examples include (56)(57)(58)(59)). These early FcgR engineering reports provide a strong justification for further engineering to increase affinity and increase the activity of engineered leukocytes.…”
Section: Fcgr Engineeringmentioning
confidence: 99%
“…Fcγ CRs have been pre-clinically tested by different groups [213][214][215][216][217][218][219]. Summarizing these studies, CD16A or a high-affinity variant (V158) was either coupled directly or via a CD8α linker and TM domain to a signaling tail, consisting of CD3ζ, 4-1BB/CD3ζ, or FcεRIγ (Figure 1).…”
Section: Fcγriii (Cd16)mentioning
confidence: 99%
“…These constructs have been retrovirally transduced or transfected [214,215] into human T cells, murine MD45 T cells, human peripheral blood NK cells, or NK-92 cells. These cells have been employed in combination with a variety of mAbs (anti-CD19, anti-CD20 (Rituximab), anti-HER2 (Trastuzumab), anti-GD2, anti-Panc1, anti-EGFR (Cetuximab, Panitumumab), or anti-CSPG4) against different cancer cells (Daudi, Raji, and adult T cell lymphoma, neuroblastoma, osteosarcoma, pancreatic cancer, colorectal cancer, and A375 melanoma cells) in vitro, as well as against lymphoma-xenografted mice [213][214][215][216][217][218][219]. Fcγ CR cells showed promising anti-tumor activity in all these studies [213][214][215][216][217][218][219], and via the attached signaling domains, activated the NF-AT pathway [213].…”
Section: Fcγriii (Cd16)mentioning
confidence: 99%